Neuromuscular training improves biomechanical deficits at the knee in anterior cruciate ligament-reconstructed athletes - Nagelli, C. V.; Wordeman, S. C.; Di Stasi, S.; Hoffman, J.; Marulli, T.; Hewett, T. E. (Clinical Journal of Sport Medicine, 2021)
Objective: Athletes who return to sport after anterior cruciate ligament reconstruction (ACLR) demonstrate persistent biomechanical and neuromuscular deficits of the knee. There is limited evidence on what effect a neuromuscular training (NMT) program has on knee biomechanics in a cohort of athletes with ACLR. Therefore, the primary aim of this study was to quantify the effect of an NMT program on knee biomechanics in a cohort of ACLR athletes. Second, the post-training knee biomechanics were compared between the cohort of ACLR and control athletes. Design: Cohort study. Setting: Controlled laboratory setting. Participants: Eighteen athletes with ACLR and 10 control athletes. Interventions: Neuromuscular training. Main Outcome Measures: Knee kinematics and kinetics during a double-limb jump-landing task. Results: There were no significant interactions ( P > 0.05) observed for the athletes with ACLR. However, there was a significant main effect of biomechanics testing session ( P < 0.05) for knee flexion angle and moments; athletes with ACLR demonstrated greater knee flexion angle and lower knee flexion moment during the post-training biomechanics testing session. Post-training comparison between the ACLR and control athletes demonstrated no significant interactions ( P > 0.05) between the groups. There was a significant main effect of group ( P < 0.05) for knee frontal angle, as athletes with ACLR landed with greater knee adduction than the control athletes. Conclusions: Significant improvements in knee sagittal plane biomechanical measures were observed after the NMT program by the athletes with ACLR. In addition, post-training comparison of the ACLR and control groups demonstrates comparable knee biomechanics.